True Volumes of Slope Failure Estimated From a Quaternary Mass‐Transport Deposit in the Northern South China Sea - Qiliang Sun; Tiago M. Alves; Xiangyang Lu; Chuanxu Chen; Xinong Xie (Geophysical Research Letters, 2018)
Abstract Submarine slope failure can mobilize large amounts of seafloor sediment, as shown in varied offshore locations around the world. Submarine landslide volumes are usually estimated by mapping their tops and bases on seismic data. However, two essential components of the total volume of failed sediments are overlooked in most estimates: (a) the volume of subseismic turbidites generated during slope failure and (b) the volume of shear compaction occurring during the emplacement of failed sediment. In this study, the true volume of a large submarine landslide in the northern South China Sea is estimated using seismic, multibeam bathymetry and Ocean Drilling Program/Integrated Ocean Drilling Program well data. The submarine landslide was evacuated on the continental slope and deposited in an ocean basin connected to the slope through a narrow moat. This particular character of the sea floor provides an opportunity to estimate the amount of strata remobilized by slope instability. The imaged volume of the studied landslide is ~1035 ± 64 km3, ~406 ± 28 km3 on the slope and ~629 ± 36 km3 in the ocean basin. The volume of subseismic turbidites is ~86 km3 (median value), and the volume of shear compaction is ~100 km3, which are ~8.6% and ~9.7% of the landslide volume imaged on seismic data, respectively. This study highlights that the original volume of the failed sediments is significantly larger than that estimated using seismic and bathymetric data. Volume loss related to the generation of landslide‐related turbidites and shear compaction must be considered when estimating the total volume of failed strata in the submarine realm.